'She's mine!' – The lived experience of becoming parents through international adoption. Issue 3 (8th September 2022) - Gatt, Mary Rose; Sammut-Scerri, Clarissa
Literature on the personal and intimate process of feeling the parent of an adopted child appears to be scant. The experience of adoptive parents' emotional and psychological process to 'feel a parent' is often overshadowed by literature focused on the experience of loss especially when parents adopt following infertility, and by literature focusing on the experiences of children pre-and-post-adoption. This article presents the findings of an Interpretative Phenomenological Analysis (IPA) with adoptive parents, exploring the intimate emotional and psychological process of becoming a parent and 'feeling a parent' through international adoption. Nine semi-structured interviews with three couples were conducted where each couple was interviewed twice, both together and separately. Six main superordinate themes emerged: Holding the child in mind and in heart before the adoption; exceeding one's expectations of connection with the child; special intimate moments consolidating the attachment process; being acknowledged as legitimate parents by the child, by their family and community; the story of how they became parents and how their child became theirs; and creating and embracing the child's larger context. The findings indicate that a systemic perspective is important when working with adoptive parents as a pivotal part of the parents' experience centred around being acknowledged by their family system as legitimate parents to their child. Practitioners also need to be sensitive to the idiosyncratic, often sensory-based attachment processes between the parents and the child in the process of becoming parents through international adoption.